Desain UI/UX Website Inventory Barang Pada Pt Dari Visi Teknologi Menggunakan Metode User-Centered Design - Conni Lestari Siahaan; Syafrianto (Prodi Teknik Elektro Universitas PGRI Banyuwangi, 2023)
In an era of rapid technological advances, there are many companies that have not utilized technology, one of which is PT Dari Visi Technology. So that the company's performance is not optimal. Therefore, we need a system to help the company's performance. The system can be a website or mobile. PT Dari Visi Technology requires a website inventory to help check goods. To produce a good website, user interface design and user experience are needed in order to determine the level of user satisfaction when using the system. This design will be designed using the User Centered Design (UCD) method where this method is focused on the needs and requirements of the user. In the UCD User Centered Design method there are 5 steps that need to be done, namely Plan the Human Centered Process, Specify the Context of Use, Specify User and Organizational Requirements, Produce Design Solutions, and Evaluate Designs against User Requirements. Following each step and stage of the UCD method will produce a design that fits the user's needs. This is proven by evaluating the design using the System Usability Scale (SUS) method to determine the user experience score. The test results using the System Usability Scale (SUS) get a result of 71,875. In the SUS range, it gets a grade C and is included in the good category